1983
DOI: 10.12938/bifidus1982.2.1_17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Administration of TOS and Bifidobacterium breve 4006 on the Human Fecal Flora

Abstract: We studied the effects of administration of TOS , a new growth factor derived from lactose for Bifidobacterium, and Bifidobacterium breve 4006 on the fecal flora of normal subjects. All of the Bifidobacterium species tested , eight reference strains and B. breve 4006 were capable of fermenting TOS in vitro , while others, 2 Bacteroides strains and 4 Lactobacillus and Enterobacteriaceae strains , showed an appreciable growth among 55 cultures tested. It was evident that TOS is not intestinally absorbed by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(93 citation statements)
references
References 22 publications
3
87
0
1
Order By: Relevance
“…Our results indicated a positive eff ect in the synbiotic group (HP-GOS+BB) during the test periods. It is known that most bifi dobacteria strains of human intestinal origin can readily use galactooligosaccharides; however, only a few strains from other genera, such as lactobacilli, possess this ability (24,26). As far as the eff ects of probiotic consumption on the bifi dobacterial population are concerned, similar results have been observed in children and adults.…”
Section: Enumeration Of Bifi Dobacteria In Rat Faecesmentioning
confidence: 73%
See 1 more Smart Citation
“…Our results indicated a positive eff ect in the synbiotic group (HP-GOS+BB) during the test periods. It is known that most bifi dobacteria strains of human intestinal origin can readily use galactooligosaccharides; however, only a few strains from other genera, such as lactobacilli, possess this ability (24,26). As far as the eff ects of probiotic consumption on the bifi dobacterial population are concerned, similar results have been observed in children and adults.…”
Section: Enumeration Of Bifi Dobacteria In Rat Faecesmentioning
confidence: 73%
“…It has been shown that 4'-galactosyl-lactose is selectively utilized by all the Bifi dobacterium strains tested, compared with lactulose and raffi nose, whose specifi city is less noticeable. Other studies have also shown that some strains of Lactobacillus, Bacteroides and Clostridium ferment GOS, and that transgalactosylated disaccharides may even be bett er substrates for these bacteria (26). Some bacterial species can ferment both 4'-and 6'-galactosyl-lactose, although there are some diff erences and the growth of bacteria is dose-dependent.…”
Section: Utilization Of Gos By Intestinal Bacteria In Vitromentioning
confidence: 99%
“…This accounts for experiments using synbiotic formulations in humans (61), rats (62,63), and other animal models (64). These findings suggest that, with few exceptions (17)(18)(19), probiotic strains are unable to compete against the resident gut microbiota, which is inherently resistant to outside colonizers (65), even when an exogenous growth substrate in the form of a prebiotic is provided.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, successful synergistic synbiotic combinations are not well established in the literature despite a large number of studies. To our knowledge, only two reports describe a synbiotic combination in which the prebiotic significantly enhanced the stability, persistence, or metabolic activity of a specific probiotic strain in vivo (17)(18)(19). As noted by Kolida and Gibson (16), this low success rate may be explained by the selection of most synbiotic combinations on an arbitrary basis, including shelf life, industrial performance, availability, and cost.…”
mentioning
confidence: 99%
See 1 more Smart Citation